2010
DOI: 10.5507/bp.2010.025
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production Disorders in Leukocytes of Patients With Recurrent Furunculosis

Abstract: Aim. The prop ensity for certain individuals to develop staphylococcal recurrent furunculosis (RF) is not fully understood. But among the reasons of its development the immune system dysfunctions are described. As in the staphylococcus elimination the main role is played by neutrophils, the objective of this study was to determine nitric oxide (NO) and reactive oxygen species (ROS) production by polymo rphonuclear leukocytes (PMNs) of patients with RF and to compare them with the response of normal cells to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…2.7. Respiratory burst NBT reduction test was performed as described previously with some modifications (Müller et al, 1981;Nabi et al, 2005;Hamaliaka and Novikova, 2010). In brief, 200 µL of neutrophil suspension (25 × 10 5 cell/mL) was mixed with 200 µL/mL of S. aureus suspension (10 8 cells/mL) and 200 µL of 0.1% NBT in PBS (pH 7.4).…”
Section: Phagocytosis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…2.7. Respiratory burst NBT reduction test was performed as described previously with some modifications (Müller et al, 1981;Nabi et al, 2005;Hamaliaka and Novikova, 2010). In brief, 200 µL of neutrophil suspension (25 × 10 5 cell/mL) was mixed with 200 µL/mL of S. aureus suspension (10 8 cells/mL) and 200 µL of 0.1% NBT in PBS (pH 7.4).…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…Bacterial ingestion was assayed by light microscopy under oil immersion. Phagocytosis activities of neutrophils were expressed as percentage of neutrophils that internalized at least one S. aureus (Hamaliaka and Novikova, 2010). 2.7.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…The NBT reduction assay was used to measure the reactive oxygen species (ROS) activity in neutrophils. 22 The obtained findings expressed that the respiratory burst of neutrophils was significantly decreased in neutrophils co-cultured with the MSCs pulsed or without caffeine, compared to neutrophils without treatment (Fig. 4).…”
Section: Resultsmentioning
confidence: 80%
“…22 In addition to encountering pathogens, different stimuli may induce the respiratory burst in neutrophils. 27 Nonetheless, when the production of ROS is excessive or inappropriate, ROS participate in severe host tissue damages and in different immunopathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that impaired chemotaxis appears only in patients with recurrent furunculosis and can serve as an independent risk factor for recurrent furunculosis. Hamaliaka and Novikova [66] demonstrated depression of nitric oxide formation at stimulation and a decrease in the production of reactive oxygen species in 58 patients suffering from recurrent furunculosis.…”
Section: Innate Immunitymentioning
confidence: 99%